Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1111/j.1553-2712.1995.tb03073.x
|View full text |Cite
|
Sign up to set email alerts
|

Proper Depth of Placement of Oral Endotracheal Tubes in Adults Prior to Radiographic Confirmation

Abstract: Objective: To determine whether a certain distance measurement on the oral endotracheal tube (ETT) at the corner of the mouth could reasonably ensure proper depth of placement in critically ill patients, without the immediate need for a confirming chest x-ray (CXR).Methods: A prospective observational cross-sectional design was used to compare ETT mark distance and radiographic location of the ETT tip. The measurement marking on the ETT at the level of the corner of the mouth was noted at the time of intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…We placed a size 8-0 ETT using direct laryngoscopy to a depth of 23 cm at the lip for male cadavers and 21 cm at the lip for the female cadaver. 9 We confirmed placement by direct visualization of the ETT between the vocal cords. 10 We inflated the ETT cuff to 20-25 cmH 2 0.…”
Section: Study Protocolmentioning
confidence: 54%
“…We placed a size 8-0 ETT using direct laryngoscopy to a depth of 23 cm at the lip for male cadavers and 21 cm at the lip for the female cadaver. 9 We confirmed placement by direct visualization of the ETT between the vocal cords. 10 We inflated the ETT cuff to 20-25 cmH 2 0.…”
Section: Study Protocolmentioning
confidence: 54%
“…For purposes of uniformity with recent studies of Roberts et al 9 and general clinical practice,'-' we chose to conform with the criteria of "adequate" tube placement defined as " 2 2 cm above the carina." However, Goodman et al proposed an alternative ideal height above the carina of 5 2 2 cm with the head in the neutral p0siti0n.l~ This was based on the findings of Conrardy et al that neck flexion advances the ETT by as much as 3.1 cm (mean 1.9 cm), and extension withdraws the ETT by as much as 5.2 cm (mean 1.9 cm), raising concerns over the safety of placing the ETT tip at precisely 2 cm above the carina, or high in the trachea."…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Roberts et. al used >2 cm from the carina for the proper placement of the ETT and concluded that placing the ETT according to the 21/23 method resulted in 97.6% correct placement [14]. More recent studies have found less beneficial results with this method suggesting this method should not be considered a more reliable method than the topographical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Had these depths been utilized, migration away from the carina would have likely induced vocal cord impingement, especially due to the longer cuff length of polyurethane HVLP ETTs [10]. In adults, multiple methods have been described for selecting the insertion level of an endotracheal tube (ETT) [3][4][5][14][15][16][17][18][19][20][21]. Owen et.…”
Section: Discussionmentioning
confidence: 99%